Science Before Dinner: Science popularization in Francoist Spain through the Los Progresos Científicos Broadcast - Boleda Jordi Ferran (HoST)
Through the case study of Manuel Vidal Españó (1905-1984), a Spanish engineer and science popularizer, this paper addresses some features of science popularization in Franco’s dictatorship (1939-1975), such as the apolitical and uncritical techno-optimism and the (dis)continuities with the previous political regime. Vidal Españó conducted science radio talks on Radio Barcelona from 1924 until the late 1960s, particularly in his show Los Progresos Científicos (the Scientific Advances), which broke the typical one-way radio communication, establishing a dynamic relationship with his audience. His techno-optimistic and uncritical stance toward science and technology was a strategic approach for navigating the Francoist regime, allowing him to express occasional dissent. In addition to analysing his adaptation to new political conditions, the article explores his connection with the public, illustrating how an effective exchange of knowledge emerged, revealing the working classes’ understanding of science and technology during Francoism.